PEMBERDAYAAN KELOMPOK USAHA SAUNG BATIK BASWET MELALUI INOVASI VARIASI MODEL DESAIN DAN TEKNOLOGI DIGITAL - Ria Manurung; Putu Samuel Prihatmajaya; David Kristian Paath (Jurnal AbdiMas Nusa Mandiri, 2023)
Saung Baswet's batik group business is categorized as a small and medium-sized enterprise. It is, therefore, very vulnerable to business continuity because it has several areas for improvement: weak capital, weak marketing, weak management skills, and weak innovation. Its produces and sells both written and printed batik. The objectives and benefits of this service activity are to create product design innovations with new patterns, namely Nagasari Flowers. They were creating direct marketing and expanding Saung Batik's marketing area at a lower cost, bringing Saung Batik closer to its customers by promoting products to be sold and creating two-way communication through the web and e-mail. Facilitate stock management and make displaying the latest products from Saung Batik easier. The results of service activities are that problems of its partners in field of batik innovation have been resolved. Design of this batik group has increased and is expected to characterize group's style. Marketing Batik products of the group becomes effective and efficient because the market reach is not limited. The solution offered is to provide Android-based online marketing and sales facilities. The batik marketing and sales application is named "E-Saung Baswet," which can reach the entire archipelago and global market as a new market share with one tool, namely a smartphone. The application is registered in Playstore, so all internet users can access it. Increased partner empowerment was achieved 100% through training on Android-based marketing and sales computer application programs and training on innovative batik designs.